2016
DOI: 10.1007/s10815-016-0850-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of large-for-gestational age birthweight in singleton siblings conceived with in vitro fertilization in frozen versus fresh cycles

Abstract: Background Children born from fresh in vitro fertilization (IVF) cycles are at greater risk of being born smaller and earlier, even when limited to singletons; those born from frozen cycles have an increased risk of large-for-gestational age (LGA) birthweight (z-score ≥1.28). This analysis sought to overcome limitations in other studies by using pairs of siblings, and accounting for prior cycle outcomes, maternal characteristics, and embryo state and stage. LGAwas 9.2-9.8 and 14.2-15.4% in 1st and 2nd births i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 68 publications
5
41
0
Order By: Relevance
“…The implantation rate for the transfer of frozen-thawed blastocysts is significantly greater than for the transfer of fresh blastocysts for all maternal age groups (SART National Summary, 2016 and2017). Moreover, the incidence of small for gestational age (SGA) babies is significantly decreased with frozen embryo transfer, while the incidence of large for gestational age (LGA) babies is significantly increased (Luke et al, 2017;Wennerholm et al, 2013). It is important to note that SGA is associated with increased overall rates of neonatal, infant and later death but there is no association between LGA and overall rates of neonatal, infant or later death (Wennerström et al, 2015;Xu et al, 2010).…”
Section: Workhop Reportsmentioning
confidence: 99%
“…The implantation rate for the transfer of frozen-thawed blastocysts is significantly greater than for the transfer of fresh blastocysts for all maternal age groups (SART National Summary, 2016 and2017). Moreover, the incidence of small for gestational age (SGA) babies is significantly decreased with frozen embryo transfer, while the incidence of large for gestational age (LGA) babies is significantly increased (Luke et al, 2017;Wennerholm et al, 2013). It is important to note that SGA is associated with increased overall rates of neonatal, infant and later death but there is no association between LGA and overall rates of neonatal, infant or later death (Wennerström et al, 2015;Xu et al, 2010).…”
Section: Workhop Reportsmentioning
confidence: 99%
“…The risk of LGA in relation to FET was assessed in 13 studies. Ten studies were eligible for inclusion in the meta-analysis (Ishihara et al, 2014;Kato et al, 2012;Li, Wang, Ledger, Edgar, & Sullivan, 2014;Luke et al, 2017;Marino et al, 2014;Pelkonen et al, 2010;Pinborg et al, 2014;Sazonova et al, 2012;Spijkers et al, 2017;Wennerholm et al, 2013). All the studies included in the meta-analysis were cohort studies.…”
Section: Lgamentioning
confidence: 99%
“…This should be considered when analyzing the increased risk of LGA in FET babies, as they normally have a higher birth order than children conceived after fresh embryo transfer. Yet, the difference in risk of LGA and macrosomia has persisted after adjustment for parity in several of the included studies (Li et al, 2014;Luke et al, 2017;Maheshwari et al, 2016;Marino et al, 2014;Pelkonen et al, 2010;Pinborg et al, 2014;Sazonova et al, 2012;Spijkers et al, 2017;Wennerholm et al, 2013).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Luke et al (27) found that in siblings sharing the same mother, children born after FET had a higher risk of LGA than their siblings born after fresh ET (27). Berntsen and Pinborg (28) evaluated the association between FET and LGA and/or macrosomia.…”
Section: Fet Pregnanciesmentioning
confidence: 99%